Island Lives - Matthew Heinz; Devon MacFarlane (SAGE Open, 2013)
In 2010-2011, the Vancouver Island Transgender Needs Assessment, a community-based, applied research project, sought to identify the health and social needs of trans people on Vancouver Island, British Columbia, Canada. An advisory board consisting of trans-identified community members and trans-service providers guided this descriptive analysis. A total of 54 individuals identifying as transgender participated in a survey modeled after the TransPULSE Ontario instrument. Of the participants, 43% identified on the transmasculine spectrum, 39% on the transfeminine spectrum, and 18% as transgender/genderqueer only. Participants were surveyed in regard to education, employment, and income; housing; health care needs and services; suicidality; violence; life satisfaction and attitudes toward self; posttransition experiences; and community belonging. They reported health care, social support, and public education/acceptance as top needs. The article concludes with a specific needs profile and a community-generated set of recommendations stressing the need for an island-based information and resourcing center.